Penerapan Alat Peraga Dalam Pelaksanaan Pembelajaran Untuk Meningkatkan Motivasi Guru Dalam Mengajar Di SDI Mbulilo’o Ende - Arifin Rego (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
This study aims to increase teacher motivation in teaching using teaching aids at SDI Mbulilo'o. Based on the description on the background, problem identification and problem limitation, the focus of this research is related to efforts to improve teacher motivation by using teaching aids at SDI Mbulilo'o Ende. This school action research was conducted at SDI Mbulilo'o Ende. Under the supervision of the researchers themselves. This type of research is the School Action Research (PTS) located at SDI Mbulilo'o Ende, which is aimed at teachers. The main reason is from the results of observations and information from the teacher, that the teaching ability of the teacher is still low. The sample in this study were all 12 teachers at SDI Mbulilo'o Ende. Based on the results of the analysis and discussion, it can be concluded that in the aspect of the principal's activity as a facilitator, he achieved a score of 27 or a percentage of 64 from all aspects of the assessment or as large as 66. % of all activities accomplished. Then in the second cycle the score obtained was 38 or with the percentage of achievement of 98% of all aspects achieved. In the aspect of teacher activity as a participant in this study, in the first cycle the score obtained from the implementation of the direction by the principal got a score of 45 or with a percentage of achievement of 56%. Then in cycle II the participation rate was 77% higher than cycle I and with an implementation score of 67. Aspects of teacher motivation during the implementation of the direction from cycle I to cycle II, teacher motivation in using teaching aids tends to increase. Where if in cycle I obtained a percentage of achievement of 54% with a sufficient category, then cycle II obtained a percentage of 77% or in the Very Good category.